An acoustic comparison of formant frequencies in individuals with normal hearing, profound and severe hearing impairment - Ozbić, Martina; Kogovsek, Damjana (Investigationes Linguisticae, 2008)
The purpose of the present research was to found out the differences in vowel formant production in 156 speakers, exactly between 46 individuals with normal hearing, 36 with severe (M=78.43, SD=16.07) and 74 with profound hearing impairment (M = 108.10, SD = 7.69). The F2 values in anterior vowel production are lower and F2 formant values are higher in the hearing impaired groups, according to the degree of hearing impairment, compared with the values of normal hearing individuals. The range of F1 from high to low vowels is smaller in the hearing impaired groups, according to the degree of hearing impairment, compared with the values of normal hearing individuals. The formant space in The F2-F1 diagram is the smallest in individuals with profound hearing impairment, and the greatest in normal hearing individuals. The formants that are influenced by the degrees of jaw opening (F1) and that are low frequency first formants ([i], [e], [O], [o], [u]) between severe hearing impairment group and normal hearing group don’t statistically significantly differ at sig. 0.05. Profound hearing impairment group statistically significantly differ from the severe hearing impairment group and from the normal hearing group. The same pattern is present in the low frequency second formants of vowels [E], [A], [O], [o], [u]. In the high frequency second formant production ([i], [e]) all the groups are statistically significantly different. Statistically significant similarity between normal hearing group and profound hearing group is observed and a statistically significantly difference between the two groups of hearing impairment in the first formant production of the vowel [E]. We can conclude that according to the cited researches the formant range, especially of F2, is reduced and the vocal formant space restricted most in the profound hearing impaired individuals.